2021
DOI: 10.1016/j.cub.2020.10.025
|View full text |Cite
|
Sign up to set email alerts
|

The Proteomic Landscape of Centromeric Chromatin Reveals an Essential Role for the Ctf19CCAN Complex in Meiotic Kinetochore Assembly

Abstract: Highlights d The composition of meiotic centromeres and kinetochores is revealed d Kinetochores undergo extensive changes between meiotic prophase I and metaphase I d The Ctf19 CCAN orchestrates meiotic kinetochore specialization d A Ctf19 CCAN-directed kinetochore assembly pathway is uniquely critical in meiosis

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 82 publications
(153 reference statements)
0
16
0
Order By: Relevance
“…Budding yeast meiotic kinetochores have a similar composition to mitotic kinetochores, with the addition of meiosis-specific factors ( (27,216); see also below). However, the pathways that govern the assembly and maintenance of kinetochores may differ in meiosis compared to mitosis since kinetochore integrity and viability in budding yeast meiosis relies on CCAN subunits that are dispensable for mitotic growth (26). In the budding mitotic yeast cell cycle, kinetochores remain fully assembled except for a brief period during S phase (127).…”
Section: Architecture Of Meiotic Kinetochoresmentioning
confidence: 99%
“…Budding yeast meiotic kinetochores have a similar composition to mitotic kinetochores, with the addition of meiosis-specific factors ( (27,216); see also below). However, the pathways that govern the assembly and maintenance of kinetochores may differ in meiosis compared to mitosis since kinetochore integrity and viability in budding yeast meiosis relies on CCAN subunits that are dispensable for mitotic growth (26). In the budding mitotic yeast cell cycle, kinetochores remain fully assembled except for a brief period during S phase (127).…”
Section: Architecture Of Meiotic Kinetochoresmentioning
confidence: 99%
“…Thus, we asked whether Spo13's function in preventing sporulation at meiosis I depends on the integrity of kinetochores. Deletion of subunits of the inner kinetochore Ctf19-complex, such as Mcm21 or Iml3, is compatible with proliferation but prevents kinetochore reassembly at entry into metaphase I, leading to massive chromosome miss-segregation (Mehta et al, 2014;Borek et al, 2021). Thus, mcm21D and iml3D mutants produce four spores of low viability (3 and 18%, respectively).…”
Section: Control Of Spore Formation By Spo13 Does Not Require Intact ...mentioning
confidence: 99%
“…In support of these results, a recent study on proteomic analysis of the mitotic and meiotic kinetochores revealed an extensive reorganization of kinetochore during meiosis, specifically during prophase I to metaphase I transition with respect to mitosis. [60] Hence, mitotically non-essential Mcm proteins play unique and critical roles in the assembly of the meiotic kinetochore. Rigorous analysis of the meiotic kinetochores using biochemical, proteomics, and imaging tools may reveal exciting results in terms of content, quantity, and temporal appearance of the constituent proteins at the kinetochore and how it may differ from a mitotic kinetochore.…”
Section: Kinetochore Assemblymentioning
confidence: 99%